PENERAPAN ASAS KESEIMBANGAN SEBAGAI INDIKATOR ASAS KEBEBASAN BERKONTRAK DALAM PERJANJIAN PEMBORONGAN PENGADAAN DAN PEMASANGAN PAKU MARKA SEBANYAK 1.000 BUAH DI RUAS SALATIGA-BOYOLALI-SOLO - Dewayani Wisnuputri, Ery Agus Priyono, Dewi Hendrawati (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
Contract agreement in the procurement and installation of 1,000 pieces of nail markings on the sides Salatiga - Boyolali - Solo made between parties who act for and on behalf of the government while the parties acting for and on behalf of the private sector. Position of the parties to the agreement is seen not balanced chartering. Persons acting for and on behalf of the government have a position / notch higher. Imbalance position both sides can lead to problems in determining the contents of the agreement to restrict freedom of contract either party. Method of approach used in the study of law is a normative legal approach, while the specification is descriptive analytical research, to provide an overview as well as analysis of the chartering agreement. In this study the authors used secondary data, while the data analysis methods used by the author is a qualitative analysis. The results of research showed that the chartering contract comply with the provisions of Article 1320 Civil Code so that the contract made is valid and binding on both parties. In chartering contract is not in accordance with the principles of balance and the principle of freedom of contract as a whole. This is because the principle of balance criteria and principles of freedom of contract is not fulfilled entirely. The first party to act for and on behalf of the government, while the second act for and on behalf of the private sector CV. Wira Adidaya. The difference in the position / positions in the chartering agreement was also influence the freedom of contract for the parties. but the rights and obligations herein shall be governed by clear and proportionate.